2018
DOI: 10.1016/j.nano.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Development of a peptide-modified siRNA nanocomplex for hepatic stellate cells

Abstract: Insulin-like growth factor 2 receptor (IGF2R) is overexpressed in activated hepatic stellate cells (HSCs) and therefore can be utilized for HSC-specific drug delivery. We recently discovered an IGF2R-specific peptide using a novel biopanning. Here, we adopted biotin-conjugated IGF2R-specific peptide, cholesterol, and vitamin A as the targeting ligands for the neutravidin-based siRNA nanocomplex to deliver PCBP2 siRNA, a potentially antifibrotic agent, to HSCs. Compared to vitamin A and cholesterol, the IGF2R-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 46 publications
4
44
0
Order By: Relevance
“…For the invasion study, the Transwell chamber was precoated with 50 μg of Matrigel, and 2 × 10 5 cells were seeded in the precoated Transwell with serum-free DMEM. After 6 hours for the migration assay and 24 hours for the invasion assay, the migrated cells were fixed with 10% paraformaldehyde, stained with 0.05% crystal violet, and counted as previously described ( 29 , 40 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the invasion study, the Transwell chamber was precoated with 50 μg of Matrigel, and 2 × 10 5 cells were seeded in the precoated Transwell with serum-free DMEM. After 6 hours for the migration assay and 24 hours for the invasion assay, the migrated cells were fixed with 10% paraformaldehyde, stained with 0.05% crystal violet, and counted as previously described ( 29 , 40 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Cy5-labeled IKBKE siRNA (50 nM) was used to form the siRNA nanocomplex. Two, 4, and 6 hours after transfection, the cells were treated with 40 μM heparin, and cellular uptake was measured using a FACS II flow cytometer (BD Instrument, NJ) ( 40 ). Confocal microscopy was performed 2 and 6 hours after transfection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that patients with low IGF2R expression had poorer prognosis after chemotherapy. Cholesterol amongst other ligands is known to bind IGF2R for delivery of Poly (rC)-Binding Protein 2 (PCBP2) siRNA to hepatic stellate cells (HSCs) [119]. These findings suggest that selected miRNAs (miR-128 and miR-223) may be potential anti-cancer drug resistance targets.…”
Section: Hsa-mir-128 and Hsa-mir-223 Potentially Regulate Genes Involmentioning
confidence: 99%
“…Curcumin, a diarylheptanoid obtained from turmeric, suppresses HSC activation by inhibiting the TGF-β signaling and downregulating the expression of tea, also exhibit anti-fibrotic effects in animals. In addition, it has been shown that siRNAs have high efficiency and specificity for liver 26,27 fibrosis.…”
Section: Introductionmentioning
confidence: 99%